Diversity scheme based hybrid FSO/RF systems in satellite-aerial-ground integrated network with outdated CSI - Xin Li; Yongjun Li; Xinkang Song; Jianjia Li; ShangHong Zhao (Scientific Reports)
Abstract Satellite-aerial-ground integrated network (SAGIN) confronts significant challenges from weather-induced impairments and transmission attenuation. To address this issue, this paper proposes a weather-dependent hybrid FSO/RF switching scheme for SAGIN, accounting for both weather effects and outdated channel state information (CSI). Specifically, three different working modes and two diversity schemes are designed to further mitigate the impact of adverse weather. System performance is evaluated using outage probability (OP), average bit-error rate (BER), and ergodic capacity (EC). Asymptotic results in the high signal-to-noise ratio (SNR) regime and under perfect CSI conditions are also provided to offer further engineering insights. Numerical results reveal that the proposed scheme achieves over 8.8 dB gain in OP and more than 8.1 dB gain in average BER.